Informe final práctica académica de psicología (2011)
Through this document, the reader may find what the result of an academic internship performed in the Psychological Care Centre was, within the area of an oriented psycho-analytical clinical psychology. It has bee also accompanied by the intervention of socio-educational psychology through a labor held in a Community called ‘La Carrilera’ in the municipality of Santa Rosa de Cabal, during a time where each of the academic training pillars were put into questioning, aiming to use the theoretical elements taken into account, so that they can be carried into the praxis context by performing psychological assessment procedures, psychotherapeutic processes, staff selection processes, and the implementation of psycho-educational workshops, among others.